Pembingkaian Berita Rumah BUMN - Yohanna Yohanna; Riris Loisa (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The world that is entering the digital era makes human life easier. Cyber media makes all kinds of news information that occurs outside and within the country we can get quickly connected to the internet. The emergence of news portals is in high demand because of their ease of access and short waiting times. Research aims to analyze framing of media coverage by Kompas.com, Tribunnews.com and Detik.com related to reporting on government programs for the period 1 September 2021 to 1 September 2022 with the number of visitors using Brand24 big data analysis. The research methods used are qualitative research and Robert N Entman framing analysis, which consist of defining the problem, diagnosing the cause, making moral judgments and treatment recommendation. Findings announce that each uses a different news frame, but is from the same source as Kompas.com, presenting news related to the words of BUMN Minister Erick Thohir, also prioritizing UMKM. We put them in order so that they can be age-adjusted for digital. The resulting product is entered into the go program. Tribunnews.com leads to news that PLN wants to achieve its target by the end of 2022, namely 1,000 MSMEs to join to go digital and Detik.com brings news from Erick Thohir words regarding the target of 30 thousand UMKM to go digital. Each media has a different point of view in framing news to influence society. Dunia memasuki era digital membuat kehidupan manusia semakin mudah. Cybermedia dengan cepat menghubungkan semua jenis informasi berita yang berlangsung di dalam dan luar negeri ke internet. Munculnya portal berita sangat diminati karena aksesnya yang mudah dan latensi yang rendah. Tujuan dari penelitian ini adalah membingkai pemberitaan media Kompas.com, Tribunnews.com, dan Detik.com terkait liputan program pemerintah 1 September 2021 hingga 1 September 2022 dengan menggunakan website Brand24. Metode penelitian yang digunakan penelitian kualitatif dengan kerangka analisis oleh framing Robert N Entman yang terdiri dari define problem, diagnose causes, make moral judgement dan treatment recommendation. Hasil kajian menunjukkan masing-masing menggunakan framing berita yang bertentangan tetapi bermula dari sumber yang sama seperti Kompas.com yang memuat berita tentang sambutan Menteri BUMN Erick Thohir untuk memprioritaskan UMKM beradaptasi dengan era digital agar produk yang diciptakan tergabung ke program go digital, Tribunnews.com membawa kabar bahwa PLN menargetkan 1.000 UMKM bergabung dan melakukan digitalisasi pada akhir tahun 2022 dan Detik.com membawakan berita dari ucapan Erick Thohir tentang target yang diinginkan yaitu 30 Ribu UMKM go online.